DNA thermodynamic pressure: A potential contributor to genome evolution - Zimic M.J. (2002)
This work was supported by a grant from CONCYTEC. We are very grateful to Holger Valqui and Oscar Moran for their critical comments, and to ClaudiaMachicado and Jose Choufor their comments and help in compiling and analysing part of the DNA sequences that support this work. Thanks also to Arman- do Bernui, Javier Espinoza, Jairzhinho Ramos, Luis Marky and Cristian Orrego, for their contribution to discussions, and especially to Mrs Ellen M. Pragen for her editorial work.